Plasticity in root symbioses following shifts in soil nutrient availability during long‐term ecosystem development. (31st December 2018) - Teste, François P.; Laliberté, Etienne
Abstract: The vast majority of terrestrial plants form root symbioses with arbuscular mycorrhizal (AM) fungi to enhance nutrient (particularly phosphorus, P) acquisition. However, some plant species also form dual symbioses involving ectomycorrhizal (ECM) fungi, with a subset of those also forming triple symbioses also involving dinitrogen (N2 )‐fixing bacteria. It has been suggested that these plants show plasticity in root symbioses to optimise nutrient acquisition depending on the type and strength of soil nutrient limitation (e.g., N vs. P), yet empirical evidence remains limited. Alternatively, the degree of investment or "preference" in particular root symbioses might simply reflect differences in inoculum potential among soils of contrasting nutrient availability, reflecting adaptations of root symbionts to different edaphic conditions. Here, we grew two co‐occurring plant species forming triple (AM/ECM/N2 ‐fixing; Acacia rostellifera ) or dual (AM/ECM; Melaleuca systena ) symbioses in soils of increasing age and contrasting nutrient availability from an Australian long‐term soil chronosequence to disentangle the relative importance of abiotic factors (e.g., soil nutrient availability and stoichiometry) and biotic factors (e.g., soil inoculum potential) in determining root colonisation patterns and functional outcomes of these multiple root symbioses. For both plant species, we found clear hump‐shaped plant growth patterns along the pedogenesis‐driven gradient in soil nutrient availability, with peak growth in intermediate‐aged soils, while high levels of mycorrhizal colonisation by the "preferred" root symbionts were maintained across all soils. We found large increases (540%) in foliar manganese concentrations with increasing soil age and declining P availability, suggesting that plants may be relying on the release of carboxylates to help acquire P in the most P‐impoverished soils. Finally, we found that soil abiotic properties, such as strong differences in soil nutrient availability, are generally more important than soil inoculum potential in explaining these shifts in our plant and root responses. Synthesis . Our study suggests that plants capable of forming multiple root symbioses show plasticity in their nutrient‐acquisition strategies following shifts in soil nutrients during long‐term ecosystem development, yet maintain a preference for certain root symbionts despite changes in soil microbial inoculum. Abstract : Our study suggests that plants capable of forming multiple root symbioses show plasticity in their nutrient‐acquisition strategies following shifts in soil nutrients during long‐term ecosystem development, yet maintain a preference for certain root symbionts despite changes in soil microbial inoculum.